2019
DOI: 10.48550/arxiv.1909.04699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feeling boundary by Brownian motion in a ball

Abstract: We provide short-time asymptotics with rates of convergence for the Laplace Dirichlet heat kernel in a ball. The boundary behaviour is precisely described. Presented results may be considered as a complement or a generalization of the famous "principle of not feeling the boundary" in case of a ball.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Note that proper description of the exponential behaviour imposed the appearance of a new non-exponential factor h(t, x, y). Above estimates have been complemented with asymptotics in [22], which revealed that the behaviour of p B (t, x, y) is in fact driven by the expression δ x+y 2 / √ t. A similar property will be observed in general lower bound (5). We refer the reader to [3,4,5,12,19,20,21] for some other recent articles focused on sharp estimates of heat kernels in other settings.…”
Section: Introductionmentioning
confidence: 61%
“…Note that proper description of the exponential behaviour imposed the appearance of a new non-exponential factor h(t, x, y). Above estimates have been complemented with asymptotics in [22], which revealed that the behaviour of p B (t, x, y) is in fact driven by the expression δ x+y 2 / √ t. A similar property will be observed in general lower bound (5). We refer the reader to [3,4,5,12,19,20,21] for some other recent articles focused on sharp estimates of heat kernels in other settings.…”
Section: Introductionmentioning
confidence: 61%